Selection of glucocorticoid-sensitive patients in interstitial lung disease secondary to connective tissue diseases population by radiomics - Feng DY; Zhou YQ; Xing YF; Li CF; Lv Q; Dong J; Qin J; Guo YF; Jiang N; Huang C; Hu HT; Guo XH; et al. (Dove Medical Press, 2018)
Ding-Yun Feng,1,* Yu-Qi Zhou,1,* Yan-Fang Xing,2,* Chuang-Feng Li,3 Qing Lv,4 Jie Dong,5 Jie Qin,3 Yue-Fei Guo,3 Nan Jiang,6 Chencui Huang,7 Hai-Tao Hu,8 Xing-Hua Guo,9 Jie Chen,10 Liang-Hong Yin,11 Tian-Tuo Zhang,1 Xing Li12 1Department of Respiration, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou 510630, People’s Republic of China; 2Department of Nephrology, The Third Affiliated Hospital of Guangzhou Medical University, Guangzhou 510150, People’s Republic of China; 3Department of Radiology, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou 510630, People’s Republic of China; 4Department of Rheumatology, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou 510630, People’s Republic of China; 5Department of Radiotherapy, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou 510630, People’s Republic of China; 6Department of Hepatic Surgery, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou 510630, People’s Republic of China; 7The Associated Laboratory for AI, Cross-strait TsingHua Research Institute and Huiying Medical Technology, Dongsheng Science and Technology Park, HaiDian District, Beijing 100192, People’s Republic of China; 8Department of Surgery, ChanCheng District Center Hospital, Foshan 528000, People’s Republic of China; 9Department of Rheumatology, The LingNan Hospital of Sun Yat-sen University, Guangzhou 510000, People’s Republic of China; 10Department of Oncology, HengYang City Center Hospital, Hengyang 421001, People’s Republic of China; 11Department of Nephrology, The First Affiliated Hospital of JINAN University, Guangzhou 510630, People’s Republic of China; 12Department of Medical Oncology and Guangdong Key Laboratory of Liver Disease, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou 510630, People’s Republic of China *These authors contributed equally to this work Purpose: The effect of glucocorticoid(s) on connective tissue disease (CTD)-related interstitial lung disease (ILD) is controversial. This multicenter study aimed to identify glucocorticoid-sensitive patients using a radiomics approach. Methods: A total of 416 CTD-ILD patients who began glucocorticoid treatment at the discretion of the attending physician, with or without cyclophosphamide, were included in this study. High doses were defined as pulsed intravenous methylprednisolone, an initial dose of 1 mg/kg/day of prednisolone or 0.8 mg/kg/day of methylprednisolone. Low doses were defined as those less than high doses. Radiomics features were manually extracted from primary lung lesions delineated on computed tomography images, and selected by variance, univariate feature selection, and least absolute shrinkage and selection operator regression model. The prediction models were developed using data from 309 patients from two centers and externally validated in 107 patients from four other hospitals. Results: Treatment response in the training and validation groups was 38.5% and 36.4%, respectively. Eleven radiomics features were selected from 1,029 features with predictive value. Random forest models built for radiomics features to predict treatment response yielded a sensitivity of 0.897. The calibration curve of a nomogram demonstrated good agreement between prediction and observation. Decision curve analysis indicated that glucocorticoid was beneficial if the predicted response rate was 50%–60% for an individual. High doses of glucocorticoids and cyclophosphamide yielded superior efficacy. Conclusion: Radiomics-based predictive models reliably identified glucocorticoid-sensitive CTD-ILD patients. Short-term, high-dose glucocorticoid with cyclophosphamide yielded promising results as a potential therapy. Keywords: radiomics, connective tissue diseases, interstitial lung diseases, glucocorticoid